Импульсный спектрозональный люминесцентный анализатор; Известия вузов. Физика; Т. 51, № 11/3 - Лисицын В. М. Виктор Михайлович; Полисадова Е. Ф. Елена Фёдоровна; Купчишин А. И.; Денисов И. П. Игорь Петрович (2009, 2009)
В фонде НТБ ТПУ отсутствует